2016
DOI: 10.1016/j.cmet.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

HIF2 α Is an Essential Molecular Brake for Postprandial Hepatic Glucagon Response Independent of Insulin Signaling

Abstract: Glucagon drives hepatic gluconeogenesis and maintains blood glucose levels during fasting. The mechanism that attenuates glucagon action following refeeding is not understood. The present study demonstrates an increase in perivenous liver hypoxia immediately after feeding which stabilizes hypoxia-inducible factor (HIF)2α in liver. The transient postprandial increase in hepatic HIF2α attenuates glucagon signaling. Hepatocyte-specific disruption of HIF2α increases postprandial blood glucose and potentiates the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 45 publications
3
49
1
Order By: Relevance
“…4d ). As ENTPD5 is also shown to activate the phosphoinositide-3 kinase/Akt pathway 36 , we the asked whether HRD1-mediated ENTPD5 protein destruction affects glucose metabolism through the insulin-Akt signaling pathway. Consistent with this hypothesis, we observed that the phosphorylation, but not total protein expression levels, of Akt, as well as its downstream targets Foxo1 and S6K, were significantly elevated in HRD1 Alb liver compared to control liver tissue, indicating that HRD1 deletion enhances the activation of the insulin signaling pathway in liver (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4d ). As ENTPD5 is also shown to activate the phosphoinositide-3 kinase/Akt pathway 36 , we the asked whether HRD1-mediated ENTPD5 protein destruction affects glucose metabolism through the insulin-Akt signaling pathway. Consistent with this hypothesis, we observed that the phosphorylation, but not total protein expression levels, of Akt, as well as its downstream targets Foxo1 and S6K, were significantly elevated in HRD1 Alb liver compared to control liver tissue, indicating that HRD1 deletion enhances the activation of the insulin signaling pathway in liver (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue iron detection was performed in formalin-fixed, paraffin-embedded sections stained with Prussian blue. For immunohistochemical analysis, frozen sections were probed with polyclonal rabbit anti-HIF-2α antibody (100-122, Novus), as previously described (47).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis. Whole-cell, nuclear, and membrane lysates were prepared as described previously (10,47). In brief, lysates were separated by SDS-PAGE, transferred onto nitrocellulose membranes, and probed overnight at 4°C with antibodies against FPN (MTP11-A, Alpha Diagnostic International [ADI]), DMT1 (NRAMP21-A, ADI), DCYTB (DCYTB-11A, ADI), and TFR1 (13-6800, Invitrogen, Thermo Fisher Scientific) for mouse tissue lysates; FPN (NBP1-21502, Novus), FTH1 (3998S, Cell Signaling Technology), GAPDH (sc-47724, Santa Cruz Biotechnology), GFP (sc-996, Santa Cruz Biotechnology), lamin…”
mentioning
confidence: 99%
“…AlbuminCre transgenic mice have been used extensively for liverspecific targeting of genes (27,28). Smad3 flox/flox:albCreϩ and T␤RI flox/flox:albCreϩ mice showed a marked improvement in PTT and glucagon tolerance tests (Fig.…”
Section: Tgf-␤1/smad3 Signaling Is Associated With Physiologicallymentioning
confidence: 99%